2017
DOI: 10.1111/odi.12760
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine oral administration as an adjunct to hyaluronic acid injection in treating temporomandibular joint osteoarthritis

Abstract: Both strategies alleviated symptoms in short term, but the patients treated with GS benefited more than those with placebo in long term, which may be due to the suppression of IL-1β and IL-6 and the stimulation of TGF-β.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 34 publications
0
18
0
9
Order By: Relevance
“…In phase 2, a full‐text reading was performed, and three studies matched the inclusion criteria . From studies not considered for inclusion, 1 was excluded because the full text was not available, while other eight did not meet the inclusion criteria . A full description of reasons for exclusion is presented in Appendix .…”
Section: Resultsmentioning
confidence: 99%
“…In phase 2, a full‐text reading was performed, and three studies matched the inclusion criteria . From studies not considered for inclusion, 1 was excluded because the full text was not available, while other eight did not meet the inclusion criteria . A full description of reasons for exclusion is presented in Appendix .…”
Section: Resultsmentioning
confidence: 99%
“…A chemopreventive action of glucosamine has also been reported in lung cancer [57]. Mechanistically, the anti-inflammatory activity of glucosamine has been linked to reduction of proinflammatory cytokines such as IL-6 or IL-1β [58].…”
Section: Glucosamine and Sucralosementioning
confidence: 96%
“…Considering the role of inflammation in OA, an anti-inflammatory agent should be beneficial in slowing down the progression of this disease [50,51]. Numerous animal [52][53][54][55] and human [56] studies reported that glucosamine possesses anti-inflammatory activities in OA. Aghazadeh-Habashi et al analyzed the effects of different doses of glucosamine (20,40,80, or 160 mg/kg/day) on rats with and found that 6-day glucosamine supplementation reduced the levels of proinflammatory cytokines IL-1, IL-6, and TNF-α and prevented the increase in the serum concentrations of nitrite, a stable metabolite of NO in rats with OA [52].…”
Section: Anti-inflammatory Activities Of Glucosaminementioning
confidence: 99%
“…In a randomized, parallel-group, double-blind clinical trial, elderly patients with temporomandibular joint OA are treated with an intra-articular hyaluronic acid injection or a combination of glucosamine hydrochloride (oral 720 mg for 3 months) and intra-articular hyaluronic acid injection [56]. Both treatments effectively alleviate the symptoms of OA after 1 month of administration, but the combination of glucosamine hydrochloride is greatly beneficial to patients with OA by further reducing the IL-6, IL-1β, and TGF-β levels [56]. Notably, the role of TGF-β in OA pathogenesis is not conclusive.…”
Section: Anti-inflammatory Activities Of Glucosaminementioning
confidence: 99%
See 1 more Smart Citation